Evaluation of the antitumour activity of local intraperitoneal hyperthermia in a model of advanced high-grade ovarian carcinoma in rats - Ya. G. Murazov; A. L. Semenov; K. Yu. Senchik; A. O. Nyuganen; A. S. Artemyeva; A. M. Belyaev (Сибирский онкологический журнал, 2022)
In our study we carried out an exploratory assessment of the antitumor activity of hyperthermic intraperitoneal perfusion (Hipep) with 0.9 % sodium chloride solution and compared it with the effect of a single normothermic intraperitoneal (i.p.) Administration of cisplatin in the maximum tolerated dose (mtd). Thirty-six mature female Wistar rats with transplanted i.p. Syngeneic ovarian carcinoma were randomized into three groups: control group (2 ml of 0.9 % sodium chloride i.p. At room temperature, n=12); cisplatin group (cisplatin 4 mg/kg i.p. At room temperature, n=12); Hipep group (open i.p. Perfusion with 0.9 % sodium chloride solution at a temperature of 40,5–41,5 °c for 45 minutes, n=12). The primary endpoint was the overall survival (os) of the animals in each of the three groups. The total peritoneal cancer index (pci), weight and degree of ascites haemorrhagia were assessed at autopsy. The median os in the control group, Hipep, and cisplatin was 19, 39, and 40 days, respectively (log-rank test р<0.0001). In comparison to the control group, the differences were statistically significant for both cisplatin (HR=0.22; 95 % ci: 0.08–0.62; log-rank test р<0.0001) and Hipep (HR=0.32; 95 % ci 0.13–0.82; log-rank test р=0.0013). There were no differences in os between the cisplatin and Hipep groups (log-rank test р=0.4853). The Hipep procedure was associated with a significant decrease in total pci, a tendency towards a decrease in the ascites weight and a higher severity of haemorrhagia. In terms of os, local hyperthermia, provided by Hipep without a cytostatic drug, was comparable with single normothermic i.p. Administration of cisplatin in mtd and exceeded the effects of the latter in relation to the development of peritoneal carcinomatosis.